The Evolutionary and Molecular Features of Broad Host-Range Necrotrophy in Plant Pathogenic Fungi - Newman, Toby E.; Derbyshire, Mark C. (Frontiers in Plant Science, 2020)
Necrotrophic fungal pathogens cause considerable disease on numerous economically important crops. Some of these pathogens are specialised to one or a few closely related plant species, whereas others are pathogenic on many unrelated hosts. The evolutionary and molecular bases of broad host-range necrotrophy in plant pathogens are not very well-defined and form an on-going area of research. In this review, we discuss what is known about broad host-range necrotrophic pathogens and compare them with their narrow host-range counterparts. We discuss the evolutionary processes associated with host generalism, and highlight common molecular features of the broad host-range necrotrophic lifestyle, such as fine-tuning of host pH, modulation of host reactive oxygen species and metabolic degradation of diverse host antimicrobials. We conclude that broad host-range necrotrophic plant pathogens have evolved a range of diverse and sometimes convergent responses to a similar selective regime governed by interactions with a highly heterogeneous host landscape.